THE EFFECT OF COMPETENCY ON EMPLOYEE PERFORMANCE USING TRAINING AS A MODERATING VARIABLE - Metriadi; Olivia Winda Ony Panjaitan (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – This research aims to provide an empirical explanation of the influence of competency on employee performance by using training as a moderating variable at the Katingan Regency Regional Drinking Water Company (PDAM). Design/Methodology/Approach – The research employs a quantitative analysis method, The sample in this study was 30 permanent employees of PDAM Katingan Regency who had attended training by determining sampling, namely purposive sampling technique. The data analysis process uses SmartPLS 4.0. Findings – The results of the study indicate that Competency has a positive and significant effect on Employee Performance and Training does not moderate the influence of Competency on Employee Performance in a positive and insignificant way at the Regional Drinking Water Company (PDAM) of Katingan Regency. Conclusion and Implications – The training could not moderate the impact of competency on employee performance. PDAM Katingan Regency employees to be able to improve their competence, especially in terms of being cooperative with other employees at work, namely by actively communicating and coordinating well with other employees.